Time Pressure and Jam Koma: Drivers of Student Burnout in Samarinda - Aini, Rohana Nur; Kesuma, Muhammad Ramadhani; Widaryo, Chandika Mahendra; Irianto, Ellen D Oktanti; Henrika, Margareth; Ariswati, Lusiana Desy (INDO PUBLISHING, 2025)
This study investigates the impact of time pressure and cognitive fatigue, locally termed jam koma, on burnout among undergraduate students in Samarinda, Indonesia. Employing a cross-sectional survey design, data were collected from 150 respondents using validated instruments to measure time pressure, cognitive fatigue, and burnout. The analysis, conducted with regression techniques, explores how these factors contribute to burnout within the collectivist cultural context of Indonesia. The findings highlight the significant roles of time pressure and cognitive fatigue as predictors of burnout, reinforcing the applicability of the Job Demands-Resources model in academic settings. The study underscores the influence of cultural expectations, such as familial and societal pressures, in exacerbating student stress. Recommendations include institutional interventions like stress management training to enhance student well-being. Limitations include the cross-sectional design and localized sample, suggesting the need for longitudinal and broader studies. This research enriches the literature on student mental health by integrating local cultural phenomena, offering insights for culturally relevant interventions in Indonesian higher education.